Evaluation of the effects of aerobic training during hemodialysis on autonomic heart rate modulation in patients with chronic renal disease - Morais, Mauro J.D.; Raimundo, Rodrigo D.; Oliveira, Fabiano S.; De Abreu, Luiz C.; Bezerra, Italla M.P.; Silva, Romeu P.M.; Rodrigues, Alliny S.; Valenti, Vitor E. [UNESP]; Pérez-Riera, Andrés R. (Wolters Kluwer, 2019)
Introduction:Chronic renal disease (CRD) affects a large portion of the population and is directly related to cardiovascular problems and hypertension, among others. Studies show that heart rate variability is directly affected by these problems. Physical-oriented exercises have been shown to be of fundamental importance in improving the adverse effects to dialysis treatment.Objective:To analyze the effects of aerobic training during hemodialysis on autonomic heart rate modulation in patients with CRD.Method:Experimental study of an open, single group clinical trial. In this clinical trial, patients with CRD will initially undergo international physical activity questionnaire and kidney disease quality of life short form protocols, as well as monitoring of heart rate systolic, and diastolic blood pressure. After evaluation of the initial parameters, patients will undergo an aerobic exercise program for 12 weeks, in 3 weekly sessions, lasting 30 minutes a session. These evaluations will allow for a greater control of the disease, and monitoring of any improvements in the quality of life and self-esteem of these patients.Ethics and dissemination:This study was approved following the guidelines and norms that regulate research involving human subjects, in Resolution No. 466/12 of the National Health Council. It was approved by the Research Ethics Committee of the Faculty of Juazeiro do Norte, with the number 1962 092. All patients who agree to participate in the research will sign the informed consent form. The results will be disseminated through peer-reviewed journal articles and conferences.
Keywords: aerobic exercise; autonomic nervous system; chronic renal disease; heart rate variability; hemodialysis